Hysteresis of MnFePSi Spherical Powder Ensembles Studied by Magneto‐Optical Imaging (Phys. Status Solidi B 2/2018). Issue 2 (12th February 2018) - Funk, Alexander; Zeilinger, Michael; Dötz, Florian; Soldatov, Ivan; Schäfer, Rudolf; Waske, Anja
Abstract : Magnetocaloric refrigeration is a cooling technology expected to offer significant energy savings. For optimal performance, magnetic materials close to a first‐order magneto‐structural transition are employed for this application. To understand hysteresis of the first‐order transition in these materials, the study of both internal and external factors is required, bridging scales from atomic interactions towards macroscopic ensemble behavior. In order to understand the origin of the volume change and magneto‐elastic interaction occurring at the firstorder transition and its impact on hysteresis in magnetocaloric systems, first‐principles calculations are carried out (see bottom right image and article no.1700465 by Gruner et al.). In‐situ measurements are another valuable tool for studying phase transitions and associated hysteresis in magnetocaloric materials, as shown in the top image on the cover. Here, the authors apply temperature‐dependent magnetooptical imaging to study the thermal hysteresis of individual magnetocaloric spheres inside a packed bed (see bottom left image and article no.1700345 by Funk et al.). Hence, using local measurements on a large number of spheres, it is possible to study local interactions between spheres and to derive ensemble behavior from individual measurements.